Identification of Equivalent Processing Conditions for Pasteurization of Strawberry Juice by High Pressure, Ultrasound, and Pulsed Electric Fields Processing - Yıldız, Semanur; Ünlütürk, Sevcan; Pokhrel, Prashant Raj; Ünlütürk, Sevcan; Barbosa-Canovas, Gustavo, V (Elsevier, 2019)
The objective of this study was to evaluate the effectiveness of high pressure processing (HPP), ultrasound (US) and pulsed electric fields (PEF) for the pasteurization of strawberry juice (SJ). Acid-adapted Escherichia coli was used to inoculate SJ prior to treatment with HPP, US, and PEF. HPP was applied at several pressures (200-400 MPa) up to 2 min while US (120 mu m, 24 kHz) was conducted at 25, 40, and 55 degrees C up to 10 min in continuous pulsing mode. In order to avoid excessive use of SJ, PEF was performed using a model solution (MS) basically composed of citric acid (8 g/L), fructose (35 g/L), glucose (35 g/L), Na2HPO4 (0.2 M) and NaCl (5%) to simulate the SJ electrical conductivity, pH, and total soluble solid (TSS). A face-centered composite design was conducted for PEF processing at different electric field intensities (EFI) (25-35 kV/cm) and treatment times (5-27 mu s). Processing conditions were selected that resulted in 5-log CFU/mL inactivation of E. coli. HPP at 300 MPa for 1 min, and US at 55 degrees C (thermosonication) for 3 min reduced E. coli in SJ by 5.75 +/- 0.52 and 5.69 +/- 0.61 log CFU/mL, respectively. PEF treatment at 35 kV/cm, 27 mu s treatment time, 350 mL/min flow rate, and 2 mu s pulse width in monopolar mode resulted in 5.53 +/- 0.00 log reduction of E. coli in MS. Likewise, E. coli population in SJ was also reduced by 5.16 +/- 0.15 log after applying the same PEF conditions to SJ. No E. coli was detected in SJ subjected to conventional thermal pasteurization at 72 degrees C for 15 s. All technologies reduced the natural microbiota below 2 log CFU/mL in terms of the total aerobic bacteria and yeast-mold counts. Thus, this study identified the equivalent conditions for the SJ pasteurization by three nonthermal processing technologies. Industrial relevance: Consumers have an increasing interest towards fresh-like food products with desirable nutritional and sensorial attributes. High pressure, ultrasound and pulsed electric field are three relevant novel nonthermal technologies as alternatives to conventional thermal treatments. This study identified the processing conditions of these three nonthermal technologies for the pasteurization of strawberry juice based on equivalent inactivation of acid-adapted E. coli. From an industrial point of view, the established processing conditions are useful references for the development of novel berry juices. In addition to microbiological safety, this study on equivalent processing allows direct efficacy and quality comparisons of a given juice pasteurized by the three nonthermal technologies under consideration.
Keywords: High pressure processing; Ultrasound; Pulsed electric fields; Equivalent processing; Strawberry juice